FIBER-REINFORCED CONCRETE FOR RIGID ROAD PAVEMENTS MODIFIED WITH POLYCARBOXYLATE ADMIXTURE AND METAKAOLIN (Advances in Civil and Architectural Engineering, 2022)
Increasing the strength and durability of road surfaces is crucial. Therefore, the concrete compressive strength, flexural strength, frost, and abrasion resistance of fiber-reinforced concrete for rigid pavements are investigated in this study an experiment is performed based on an optimal plan, in which four factors of concrete composition are varied: the amounts of Portland cement, polypropylene fiber, metakaolin, and polycarboxylate type admixture. Experimental statistical models for investigating the effects of composition factors on concrete properties are established. It is discovered that owing to the use of metakaolin and a superplasticizer, the concrete compressive strength increases. Furthermore, the use of modifiers and fiber reinforcement increases the flexural strength, frost resistance, and wear resistance of concrete. X-ray phase analysis of the fiber-reinforced concrete structure confirm the effectiveness of the modifier effect, in particular the positive role of metakaolin as an active pozzolana. The developed fiber-reinforced concrete for rigid pavements with rational modifiers, depending on the Portland cement content, exhibits compressive strengths from 55 to 70 MPa, flexural strengths from 8 to 9.5 MPa, frost resistances from F350 to F450, and abrasion resistances from 0.3 to 0.4 g/cm2. Such properties ensure the high durability of fiber-reinforced concrete and allow it to be used on road pavements that support heavy loads and traffic.